Hysterectomy: Indications and depression as adverse psychological consequence - Syed, Tehmina Parveen; Devi, Rekha; Kumar, Rakesh; Devi , Ramna (Journal of Pakistan Psychiatric Society, 2021)
Abstract: Hysterectomy is not a life threatening procedure but Women who undergo hysterectomy face a multitude of physical and psychosocial problems, estrogen deficiency (in case of removal of ovaries) may have more detrimental effect on women’s health. Feeling of loss of femminity is also a main cause of anxiety and depression after hysterectomy. Studies showed that patient education about potential outcomes after hysterectomy may enhance their satisfaction with the procedure and also less or no long-term psychological morbidities, 10, 11 but still the association between hysterectomy and subsequent, long-term psychological health is not well defined. The present study explores the common indications of hysterectomy and its subsequent long-term psychological effects. OBJECTIVE: To demonstrate common indications of hysterectomy in our hospital. To assess long-term psychological impact of hysterectomy. Materials and methods: We conducted prospective observational study from Jan 2018 to July 2020. Total 112 hysterectomies were performed during this period. We observed common indications of hysterectomies and assessed long-term psychological effects by using DSM-V and Beck Depression Inventory questionnaire. Results: In Peri-menopausal women, the most common indication of hysterectomy was heavy menstrual bleeding and majority were due to uterine fibroids, while, in post-menopausal women the main reason was post-menopausal bleeding. Our study revealed that women who experienced premature menopause had developed severe depression after their hysterectomy, hence they require more support and counselling to maintain good psychological health.